PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, DAN LEVERAGE, TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Jasa dan Transportasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2014) - Nofiana Febriati; Kirmizi Kirmizi; Azhari S. Azhari S. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to examine the impact of independence board, audit committee, institutional ownership, corporate size, profitability, and leverage against Tax Avoidance. The population of this research are service and transportation companies that listed on Indonesian Stock Exchange during 2012- 2014. The sample used in this research determined by purposive random sampling method, and totally amounted 25 companies that match to the criteria that have been set. The analysis method that used in this research is double linear regression analysis test assisted with SPSS Windows Ver 20.Result of this research indicated that profitability and leverage significantly affect tax avoidance, and independence board, audit committee, institutional ownership, and corporate size which proxies corporate governance have no effect on tax avoidance. Result of coefficient of determination (adjusted R2 ) is 0,625, it means that the overall effect of independent variables against tax avoidance is 62,5% while the remaining amounted 37,5% is influenced by the other independent variables that not used in this research.Keywords : Audit Committee, Corporate Governance, Corporate Size, Independence Board, Institutional Ownership, Leverage, Profitability, Tax Avoidance.